PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - I Putu Krisnanda Wardana; Isthi Wahyuning Tyas (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Timeliness is a measure of transparency and the quality of financial reporting. The period between the company's reporting date and the date of public disclosure of financial information is an indicator of the quality of the reported financial information. This study aims to find empirical evidence about the factors that affect the timeliness of the submission of financial statements of banking companies listed on the Indonesia Stock Exchange (BEI). The population1 of this study are of banking companies listed on the Indonesia Stock Exchange in 2019-2021. This research is quantitative with a total population of 43 companies and total sample of 129 companies determined by purposive sampling. The analytical method used is to use a logistic regression model. With this model it can be seen the influence of all factors. The factors tested in this study include Profitability, Company Size, and Leverage. This research is using secondary data and data analysis techniques using SPSS 25. The result showed Profitability were not proven to have a significant effect on the timeliness of financial reporting, Company Size variables had positive on the timeliness of financial reporting, Leverage variables had negative on the timeliness of financial reporting. Keywords: Profitability, Company Size, Leverage, and timeliness of financial reporting